Additional Use of Prostacyclin Analogs in Patients With Pulmonary Arterial Hypertension: A Meta-Analysis - Wang, Pengwei; Deng, Jiaxin; Zhang, Quanying; Feng, Hongyan; Zhang, Yongheng; Lu, Yizhong; Han, Lizhu; Yang, Pengfei; Deng, Zhijian (Frontiers in Pharmacology, 2022)
Background: Combination therapy has become an attractive option in pulmonary arterial hypertension (PAH) treatment. The aim of this study was to investigate whether additional use of prostacyclin analogues could exert any additional benefits over background targeted therapies in PAH patients. Methods: Searches were performed on PubMed, Embase and ClinicalTrials.gov from inception to October 1, 2021. Randomized controlled trials were included if patients had been treated with prostacyclin analogues-containing combination therapy and compared with the use of other PAH-specific background therapies. The bias risk and statistical analysis of the enrolled studies were performed with RevMan 5.1. Sensitivity analysis and funnel plot were used to evaluate the stability and publication bias, respectively. PROSPERO registered number CRD42021284196. Results: Ten trials involving 1828 patients were included. Prostacyclin analogues treatment was associated with greater improvement in clinical worsening (risk ratio [RR], 0.70; 95% confidence interval [CI], 0.57 to 0.86), 6-minute walk distance (mean difference [MD], 37.17 m; 95% CI, 3.01 to 71.33 m), NYHA/WHO functional class (RR, 1.58; 95% CI, 1.21 to 2.05), mean pulmonary artery pressure (MD, -9.23 mmHg; 95% CI, -17.44 to -1.03 mmHg) and cardiac index (MD, 0.41 L/min/m2; 95% CI, 0.26 to 0.55 L/min/m2) than control group. No significant differences in pulmonary vascular resistance (MD, -137.22 dyn·s/cm5; 95% CI, -272.61 to -1.84 dyn·s/cm5) and all-cause mortality (RR, 0.96; 95% CI, 0.57 to 1.61) were found between prostacyclin analogues group and control group. Of note, more adverse events (RR, 1.07; 95% CI, 1.02 to 1.13) occurred in the prostacyclin analogues group, but no significant increase in serious adverse events (RR, 1.25; 95% CI, 0.75 to 2.11). Conclusion: Additional prostacyclin analogues treatment exerted benefits on clinical worsening, exercise capacity, functional class, mean pulmonary artery pressure and cardiac index in PAH patients. But it was associated with overall risk of adverse events.